Dynamic regulation of receptor-modulated endothelial NADPH oxidases - Markus Waldeck-Weiermair; Apabrita A. Das; Taylor A. Covington; Jennifer L. Meitzler; James H. Doroshow; Junyi Duan; Yick W. Fong; Jonas Kaynert; Shambhu Yadav; Tanoy Dutta; Fotios Spyropoulos; Arvind K. Pandey; et al. (Proceedings of the National Academy of Sciences, 2026)
The stable reactive oxygen species (ROS) hydrogen peroxide (H 2 O 2 ) acts as a key signaling molecule for many vital intracellular pathways. In diverse cell types, surface receptors control intracellular H 2 O 2 levels by modulating the activity of NADPH oxidases (NOX), a family of enzymes responsible for ROS synthesis. Most NOX isoforms are regulated through the reversible assembly of protein subunits to form an active oligomeric complex. The NOX isoforms NOX2 and NOX4 are expressed in endothelial cells and generate H 2 O 2 in response to activation of cell surface receptors. The GPCR agonist histamine activates NOX2 independently of NOX4, but the H 2 O 2 response to activation of the receptor tyrosine kinase agonist vascular endothelial growth factor (VEGF) involves both NOX2 and NOX4 by unknown mechanisms [M. Waldeck-Weiermair et al. , Redox Biol. 58 , 102539 (2022); M. Waldeck-Weiermair et al. , Redox Biol. 73 , 103214 (2024)]. Here, we show that endothelial NOX4 is localized to the endoplasmic reticulum (ER). We define the redox states of various subcellular locales in the vascular endothelium and demonstrate that NOX2 is responsible for cytosolic H 2 O 2 signaling, whereas NOX4 contributes to H 2 O 2 generation in the endoplasmic reticulum. Using biochemical assays and structural modeling, we further identify a previously unrecognized regulatory interaction in which the NOX2 subunit p67 associates with NOX4. VEGF stimulation induces dynamic dissociation of p67 from NOX4, unveiling a “cross talk” between NOX isoforms that coordinates the activation of both NOX2 and NOX4 and thereby produces compartment-specific H 2 O 2 signals. This mechanism underscores the pivotal roles of NOX2 and NOX4 subunit interactions in endothelial redox homeostasis controlling cell survival, proliferation, and migration.